Genomic homologous recombination in planta. - Gal, S (1991)
A system for monitoring intrachromosomal homologous recombination in whole plants is described. A multimer of cauliflower mosaic virus (CaMV) sequences, arranged such that CaMV could only be produced by recombination, was integrated into Brassica napus nuclear DNA. This set-up allowed scoring of recombination events by the appearance of viral symptoms. The repeated homologous regions were derived from two different strains of CaMV so that different recombinant viruses (i.e. different recombination events) could be distinguished. In most of the transgenic plants, a single major virus species was detected. About half of the transgenic plants contained viruses of the same type, suggesting a hotspot for recombination. The remainder of the plants contained viruses with cross-over sites distributed throughout the rest of the homologous sequence. Sequence analysis of two recombinant molecules suggest that mismatch repair is linked to the recombination process.